Long-term prognosis of zero coronary artery calcium score in symptomatic low to intermediate risk patients. (20th July 2021) - Kamerman, M; Timmer, JR; Ottervanger, JP; Van Dijk, JD; Knollema, S; Jager, PL; Nasir, K; Mouden, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose/background: Absence of coronary artery calcium (CAC) has shown an excellent long-term prognosis with a low number of events in asymptomatic patients. However, long-term prognosis in stable symptomatic patients undergoing SPECT MPI with a zero CAC score remains unknown. Methods:  We retrospectively analyzed 1600 low- to intermediate risk symptomatic patients referred for clinically indicated cardiac SPECT/CT imaging with a CAC score of zero. Long-term follow-up data were collected for the occurrence of all-cause mortality and major adverse cardiac events (MACE: any revascularization, non-fatal myocardial infarction or cardiac death). Results:  The mean age was 54.7 ± 11 years and 71% were female. More than half of the patients (51%) had 2 or more traditional risk factors, mainly a positive family history (55%) and/or hypertension (49%).  Overall 12% had perfusion abnormalities, 98% of them were mild. During a mean follow-up of 8.6 ± 1.9 years MACE occurred in 42 patients (0.3% per year) and 85 patients died (0.6% per year). The predominant cause of death was cancer (40%). Cox proportional hazard model revealed that increasing age (HR: 1.05, 95% CI: 1.02-1.09) and current smoking status (HR: 3.58, 95% CI: 1.72-7.37) were independent predictors of MACE.  Pre-test probability (HR: 1.52, 95% CI: 0.82-2.82) and abnormal SPECT result (HR: 1.72, 95% CI: 0.88-3.37) were not associated with an increased risk of MACE. Conclusion: Overall, stable symptomatic patients with a low-to intermediate risk and a CAC score of 0 have a) low likelihood of abnormal SPECT, and  b) excellent long-term prognosis of 0.3%/year irrespective of baseline pre-test probability and SPECT abnormalities. These findings support notion of CAC as gatekeeper for appropriate patient selection to avoid un-necessary downstream testing.